The ratio of the subjective audiometry in patients with acoustic trauma and “noisy” production workers - Shydlovska T.А.; Petruk L.H. (Medičnì Perspektivi)
Introduction: The problem of diagnosis and treatment of sensorineural hearing loss (SHL), including forms developed under the influence of noise, takes one of the leading places in ot¬olaryngology. However, there are not many studies on acoustic trauma, although this problem has recently become more and more important. Objective: A comparison of subjective audiometry in patients with sensorineural hearing loss after acute acoustic trauma and chronic noise exposure. Materials and methods. In the work the results of exa¬mination of 84 patients with acoustic trauma, 15 healthy as the control group and 15 workers employed on 'noise' occupations as a comparison group are given. Subjective audiometry was fully carried out by clinical audiometer AC-40 «Interacoustics» (Denmark). Hearing indices were investigated in the conventional (0,125-8) kHz and extended (9-16) kHz frequency bands. Results: Subjective audiometry showed a reduction in sound perception in all patients. Ac¬cor¬ding to the threshold tone audiometry in patients with acoustic trauma hearing thresholds were authentically (P <0,05) increased by 4, 6 and 8 kHz tones of conventional (0,125-8) kHz frequency band and by 14-16 kHz tones of the extended (9-16 kHz) in comparison with the control group, as with workers employed on noise occupations. All the examined patients had deterioration of speech-test audiometry and above-threshold audiometry. Conclusions: According to su¬b¬jective audiometry, the type similar disorders of auditory function are in patients with acoustic trauma as in patients with long-term noise exposure, but they are more pronounced and develop much faster. The most informative features which show the origin and progression of hearing loss in patients with acoustic trauma are: increasing hearing thresholds by 14 and 16 kHz tones of the extended (9-16 kHz) frequency band and by 4, 6 and 8 kHz tones of con¬ven¬tional (0,125-8) kHz frequency band plus the reduction of differential thresholds (DT) according to the Lusher’s method at 4 kHz.